Antara Khilāfah dan Pancasila;‎ ‎(Sebuah Jawaban terhadap Anggapan Khilāfah anti Pancasila)‎ - Ahmad Subekti Jiwandana (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2018)
It seems like there is no end of the discussion of khilāfah (Caliphate). In Indonesia, recent ‎issues concerning khilāfah encompasses a claim that khilāfah rejects or in a confrontation ‎with Pancasila.  Pro and Contra ideas came out bringing several argumentation from ‎each sides, and it is clear that a detail discussion with valid analysis and authentic ‎evidences are truly demanded to argue, is system of khilāfah contrast with Pancasila or in ‎reverse? To answer such a question, this paper will explain concept of khilāfah from ‎perspective of Taqiyyudin al-Nabhani, one of Muslim figure defending khilāfah. His idea ‎and discourse has spread in various countries including Indonesia. The argumentations ‎consist in this paper are: the origin of concept of khilāfah, figur of chaliph, system of ‎Daulah Islamiyah, foreign and domestic political policy according to khilāfah, and an ‎effort to esablish khilāfah according to Taqiyyudin al-Nabhani. Moreover, this paper will ‎elaborate the similarities between khilāfah and Pancasila in their government system as ‎well. Through a discussion referring to Nabhani’s writing such as Nizam al-Islam, Nizam ‎al-Hukm fi al-Islam, al-Muwassa’ wa Munaqqah bi ‘abdil al-Qadim Zallum, al-Daulah al-‎Islamiyyah, and Al-Syakhsiyah al-Islamiyyah, it is concluded that khilāfah does not ‎contradict or confront Pancasila. From its historical aspect, the rising of khilāfah and ‎Pancasila utilizes a conformable principles such as prioritizing a principle of deliberation, ‎religious morality and spirituality, social justice and welfare.